Impacts of Stress‐dependent Hydraulic Properties on Hillslope‐Scale Groundwater Flow - Ronny Figueroa; Ronan Abhervé; Landon J. S. Halloran; Benoît Valley; Clément Roques (Geophysical Research Letters)
Abstract Groundwater flow at the hillslope scale is controlled by hydraulic properties and topography. Geological media are inherently heterogeneous, with properties depending on both lithology and external factors such as weathering, erosion, and tectonic activity. The effects of stress‐dependent variations in porosity and hydraulic conductivity on groundwater flow and residence times remain unexplored. Using process‐based hillslope models, we demonstrate how external lateral stresses cause significant variations in stress and strain, particularly on slopes steeper than 30%. These stresses reorganize porosity and hydraulic conductivity, with compressive regimes reducing these properties at valley bottoms and tensional regimes elevating values at crests. This redistribution of porosity and hydraulic conductivity leads to a channeling of groundwater flow near the surface. Channeling increases discharge rates in the upper seepage zone and the proportion of rapid flows. Our results highlight geomechanical‐hydraulic property relationships as critical controls on critical zone processes in mountain settings.